A self-consistent FLUKA algorithm for studying the response of passive dosimeters based on CR-39 track detectors in fast neutron fields. (November 2020) - Bolzonella, M.; Caresana, M.; Ferrarini, M.
Abstract: The work presents a self-consistent algorithm to study the response of passive neutron dosimeters based on CR-39 detectors, through simulations with the FLUKA code (version 2011.2x.5). The various assumptions and features of the algorithm are described and the simulated results are compared to some experimental data referred to monochromatic and quasi-monochromatic neutron fields to show the potentialities and the limits of the procedure. Moreover, the response function of the dosimeter for normally impinging neutron fields is shown. In general, the algorithm turns out to work properly in estimating the dosimeter response, thus allowing to characterize the device in various situations in the frame of possible applications as an environmental and/or personal dosimeter. Highlights: a) Algorithm for simulating successfully the response of dosimeters based on CR-39 devices is discussed. b) Response function in terms of ambient dose equivalent is obtained. c) Results are consistent with experiments, and extend the energy range.